Depressive Symptoms Are Associated With Decreased Quality of Life and Work Ability in Currently Working Health Care Workers With Recurrent Low Back Pain. Issue 9 (11th September 2022) - Virkkunen, Tarja; Husu, Pauliina; Tokola, Kari; Parkkari, Jari; Kankaanpää, Markku
Abstract : For health care workers, low back pain (LBP) is one of the leading causes of work disability and early exit from the labor market. Moreover, depressive symptoms are common with LBP, and the treatment of these symptoms is a crucial step in improving the quality of life and work ability of health care workers. Abstract : Objective: This study investigates the association between depressive symptoms and multisite pain and health-related quality of life and work ability in currently employed health care workers with recurrent low back pain (LBP). Methods: Multisite pain, depressive symptoms, quality of life, and work ability were assessed by validated questionnaires. A generalized linear model was used for statistical analysis. Results: Notably, 28% of female health care workers with LBP had at least moderate levels of depressive symptoms. Depressive symptoms were significantly associated with decreased health-related quality of life and work ability. Multisite pain was not significantly associated with work ability. Conclusions: Depressive symptoms are relatively common in female health care workers with LBP, and treatment of these symptoms may be crucial to improve their work ability.